Early Effects of P-15 on Human Bone Marrow Stem Cells - Francesco Carinci; Francesca Farinella; Annalisa Palmieri; Ambra Girardi; Vincenzo Sollazzo (eJournal of Oral Maxillofacial Research)
Objectives: Peptide-15 (P-15) is an analogue of the cell binding domain of collagen. P-15 has been shown to facilitate physiological to process in a way similar to collagen, to serve as anchorage for cells, and to promote the binding, migration and differentiation of cells. However, how P-15 alters osteoblast activity to promote bone formation is poorly understood. To study the osteoinductive properties of peptide P-15, we analyzed the expression levels of bone related genes in human mesenchymal stem cells treated with this biomaterial.Material and methods: Using real time Reverse Transcription-Polymerase Chain Reaction the quantitative expression of specific genes, like transcriptional factors (RUNX2 and SP7), bone related genes (SPP1, COL1A1, COL3A1, BGLAP, ALPL, and FOSL1) and mesenchymal stem cells marker (ENG) were examined.Results: P-15 causes a considerable induction of osteoblast transcriptional factor like osterix (SP7) and of the bone related genes osteopontin (SPP1) and osteocalcin (BGLAP). In contrast the expression of endoglin (ENG) was markedly decreased in stem cells treated with P-15 respect to untreated cells, indicating the differentiation effect of this biomaterial on stem cells.Conclusion: The present study shows the effect of P-15 on mesenchymal stem cells in the early differentiation stages: P-15 is an inducer of osteogenesis on human stem cells as indicated by the activation of bone related markers SP7, SPP1 and BGLAP.The results may allow a better understanding of the molecular mechanism of bone regeneration and as a model for comparing other materials with similar clinical effects.